Продуктивность и структура травостоя как параметры оценки срока косьбыестественных сенокосов - Саргсян, Анюта; Межунц, Баграт; Гарибян, Инна; Саргсян, Татевик (ՀԱԱՀ հիմնադրամ)
Հոդվածում ներկայացված են բնական խոտհարքներում բույսերի ակտիվ աճի շրջանում ստացվող բերքի ծավալը եւ հիմնական բուսախմբերի մասնաբաժինն ըստ տեղանքի պայմանների ու խոտհնձի ժամկետի: Դաշտային հետազոտություններն իրականացվել են ծովի մակերևույթից 700 և 950 մ բարձրությունների վրա գտնվող և տարբեր դիրքադրության (հյուսիսային կամ արևելյան) երկու փորձադաշտերում: Ըստ ուսումնասիրությունների՝ գրանցվել է խոտհարքների բարձր բերքատվություն (խոտհնձի ժամանակ՝ մոտ 380 գ/մ2), բարձրարժեք հացազգիների և բակլազգիների տեսակարար կշիռը կազմել է 43 և 33 %, իսկ մոլախոտերով հարուստ տարախոտերինը՝ 24 %: Տեղանքի պայմաններն էական ազդեցություն չեն գործել բերքի վրա, սակայն հացազգիների առավելագույն մասնաբաժին գրանցվել է համեմատաբար բարձրադիր, իսկ բակլազգիների՝ ցածրադիր, հիմնականում հյուսիսային դիրքադրության խոտհարքներում: Natural hayfields play an important role in sustainable agricultural development, providing high-quality forage for cattle and contributing to ecosystem balance. Proper timing and frequency of haymaking help preserve the reproductive potential of meadows while enhancing both the quantity and quality of forage. This article presents data on the amount of biomass harvested during the active growth period of plants in natural hayfields, with a focus on the proportion of major plant groups depending on site conditions and mowing periods. Field studies were conducted on hayfields at two experimental sites located at different elevations (700 and 950 meters above sea level) and with different expositions (north and east). The studies revealed that these hayfields had high yield potential, with an average biomass of about 380 g/m² at harvest time. The plant communities were dominated by valuable grasses (43 %) and legumes (33 %), with forbs (24 %) being less prevalent. However, the presence of weeds was relatively high. Land conditions, including elevation and exposition, had a negligible effect on overall yield. Nonetheless, a higher proportion of grasses was found at the higher elevation, while legumes were more common at lower elevations, especially in areas with northern exposition․
Keywords: Агрономия и аг роэкология